2019
DOI: 10.5958/0974-0279.2019.00008.9
|View full text |Cite
|
Sign up to set email alerts
|

Coffee value chains in India: exploring sustainability oriented markets

Abstract: Indian coffee sector is at an important point of transition, wedged between quality and value segments of the market. The trend towards Robusta has reduced the share of Arabica coffee resulting in moving away from the quality segment of the market. The value chain analysis of conventional, certified, and organic coffee indicated that chains for coffee are largely diffuse in nature, with limited coordination in terms of quality and specifications in the conventional chain. Coordination is stronger in certified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Physiological parameters of onion seed, namely, germination (%), seedling length (cm), seedling dry weight (mg) and seed viability (%) declined with increase in the age of the seed in all of the three cultivars under study. Among the three cultivars best performing cultivar was Hisar Onion-4 ( 3 in fresh seed (83, 83.67 and 84.67%) reduced to 9.33, 11 and 12.67% in the four-year-old seed ( Figure 1A). Due to the natural ageing, the maximum reduction in germination and viability was observed in V 1 compared to V 2 and V 3 .…”
Section: Seed Physiological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological parameters of onion seed, namely, germination (%), seedling length (cm), seedling dry weight (mg) and seed viability (%) declined with increase in the age of the seed in all of the three cultivars under study. Among the three cultivars best performing cultivar was Hisar Onion-4 ( 3 in fresh seed (83, 83.67 and 84.67%) reduced to 9.33, 11 and 12.67% in the four-year-old seed ( Figure 1A). Due to the natural ageing, the maximum reduction in germination and viability was observed in V 1 compared to V 2 and V 3 .…”
Section: Seed Physiological Parametersmentioning
confidence: 99%
“…The productivity of onion in India is very low when compared with Ireland (30.5 t/ha), USA (66.82 t/ha), Spain (52.48 t/ha) and China (22.08 t/ha) [2]. As the area planted with onion is increasing, the demand for high-quality seed is growing [3]. Availability of viable and vigorous seed at the time of planting is of paramount importance for accomplishing production targets [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Severová and Bendl (2013) studied the behaviour of cartels in the food market and found that most of the trade happens in oligopolistic markets. Chengappa et al (2012) found the role of cartelization by traders to manipulate the prices and restrict the entry of new competitors in onion markets in Maharashtra and Karnataka. Rahman (2015) attempted to test for asymmetric wholesale retail price transmission in India using the threshold auto-regression and momentum threshold auto-regression models.…”
Section: Introductionmentioning
confidence: 99%
“…Murthy and Subrahmanyam (2003) studied the demand and supply analysis of onion under uncertain production situations. Chengappa et al (2012) studied the competitiveness of major onion markets in Karnataka and Maharashtra. Saxena et al (2020) studied that how price shocks are transmitted from the consumers' markets to producers' markets.…”
Section: Introductionmentioning
confidence: 99%